Demyelination and neurodegeneration early in experimental autoimmune encephalomyelitis contribute to functional deficits in the anterior visual pathway - Maria T. Sekyi; Micah Feri; Shane Desfor; Kelley C. Atkinson; Batis Golestany; Fernando Beltran; Seema K. Tiwari-Woodruff (Scientific Reports)
Abstract Impaired visual function is a prevalent feature of optic neuritis (ON) in multiple sclerosis (MS). Abnormal visual evoked potential (VEP) findings of increased latencies, reduced amplitudes and abnormal waveforms as well as decreased retinal nerve fiber layer (RNFL) assessed by optical coherence tomography (OCT) are hallmarks of ON-induced visual dysfunction. Here we utilized the experimental autoimmune encephalomyelitis (EAE) mouse model of MS to investigate the functional and pathological progression during early (before any clinical symptoms), peak (initial maximal clinical symptoms), and late (chronic disease for > 3 weeks) disease stages. Demyelination and initial stages of axon damage were observed in early EAE. Significant demyelination, inflammation, increased axon damage and impaired P1/N2 amplitudes and latencies by VEP were seen in middle and late EAE groups. A decrease in RNFL thickness by OCT was observed only during late EAE. NanoString analysis of optic nerves from late EAE indicated elevated inflammation-related genes, reduced myelin-related genes, and changes in axon degeneration-related genes. Early inflammatory demyelination and functional deficits of the visual pathway, if untreated, may lead to severe irrecoverable axon damage in EAE. These studies potentially help explain the progression of visual dysfunction during MS.